Dolor abdominal en Urgencia - Betancur G., Raúl; Salazar A., Juan P.; Brinkmann B., Manuela; Quezada I., Ricardo (Revista Hospital Clínico Universidad de Chile, 2014)
Abdominal pain is one of the most important and frequent complaints that seek resolution in the emergency departments arround the globe. Despite its high frequency and the improvement in diagnostic resources, delays and pitfalls are still present now a days. Emergency Medicine approach towards these patients focusses in ruling out severe and life threatening pathology, and appropriate management (amount of exams either blood tests or images), and pain medication of those patients which are rated as with minor risk. One of the most important goals is fast and effective pain management, while the use of new complementary diagnostictools allow risk stratification, specially considering atypical presentations, as elderly population, immunocompromised patients or those with previous bariatric surgery.